2018
DOI: 10.1136/annrheumdis-2018-214127
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analysis reveals shared new loci in systemic seropositive rheumatic diseases

Abstract: ObjectiveImmune-mediated inflammatory diseases (IMIDs) are heterogeneous and complex conditions with overlapping clinical symptoms and elevated familial aggregation, which suggests the existence of a shared genetic component. In order to identify this genetic background in a systematic fashion, we performed the first cross-disease genome-wide meta-analysis in systemic seropositive rheumatic diseases, namely, systemic sclerosis, systemic lupus erythematosus, rheumatoid arthritis and idiopathic inflammatory myop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 54 publications
1
69
0
1
Order By: Relevance
“…In Annals of Rheumatic Diseases , Acosta-Herrera et al have reported their results from a genome-wide meta-analysis of four systemic seropositive rheumatological immune-mediated inflammatory diseases (IMIDs) including systemic sclerosis (SSc), systemic lupus erythematosus (SLE), RA and idiopathic inflammatory myopathies (IIM) 9. Autoantibody production is one of the main features of these diseases.…”
mentioning
confidence: 99%
“…In Annals of Rheumatic Diseases , Acosta-Herrera et al have reported their results from a genome-wide meta-analysis of four systemic seropositive rheumatological immune-mediated inflammatory diseases (IMIDs) including systemic sclerosis (SSc), systemic lupus erythematosus (SLE), RA and idiopathic inflammatory myopathies (IIM) 9. Autoantibody production is one of the main features of these diseases.…”
mentioning
confidence: 99%
“…Here, we adopted the fastBAT method which was a robust set-based association test computing the P-value of a gene with a number of SNPs from an approximated distribution (Bakshi et al, 2016). 431 genes located at 50 loci reached genome-wide significance in the RA dataset, including 17 known loci (Acosta-Herrera et al, 2019;Buniello et al, 2019;Eyre et al, 2012;Plenge et al, 2005;Raychaudhuri et al, 2009;Zhu et al, 2016) and 33 novel loci which should be examined in future replication studies (Table S4).…”
Section: Gene-based Comparisonmentioning
confidence: 99%
“…Autoimmune diseases are a group of disorders characterized by the loss of immune self-tolerance of the organism, generating autoantibodies against its own tissues [8]. In the cases where there is a systemic autoantibody response and the musculoskeletal system is affected, the disorders are known as 'systemic seropositive rheumatic diseases', which includes rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), systemic sclerosis (SSc), idiopathic inflammatory myopathies (IIM), among others [8,9]. In general, these conditions are considered as seropositive, however it is worth mentioning that they can manifest without the presence of autoantibodies in a smaller proportion of patients.…”
Section: Systemic Seropositive Rheumatic Diseases and Drug Repositioningmentioning
confidence: 99%
“…A recent report by Acosta-Herrera et al summarizes the main findings in the cross-disease meta-analysis in systemic seropositive rheumatic diseases to date [16]. An interesting study to highlight is the one combining four of these conditions, namely SSc, SLE, IIM and RA, where the authors evaluate drug targets indicated for prevalent diseases such as RA, and provide possibilities of being repurposed in genetically related, less prevalent or rare diseases such as SSc [8]. The main results of these studies are summarized in Table 1.…”
Section: Systemic Seropositive Rheumatic Diseases and Drug Repositioningmentioning
confidence: 99%